Morbimortalidade em crianças e adolescentes vítimas de acidentes automotivos - Lino, Thiago Henrique de Araujo (2014)
Objective: The aim of this work was to study the morbidity and mortality related to automotive accidents involving children and adolescents. Methods: The first study consisted of a systematic review in four databases (SciELO, MEDLINE, Scopus and Web of Science) involving related association between socioeconomic and environmental conditions and automobile accidents involving children and adolescents articles. A second study with cross- sectional design was carried out in the Forensic Institute of Campina Grande-PB, collecting information from children and adolescents, their injuries and accidents from January 2008 to December 2011. Descriptive and inferential statistics were applied (α=5%). Results: In systematic review of 748 articles identified, 28 were considered eligible, but six studies met the inclusion criteria. Despite methodological weakness identified, it was observed evidence on the association socioeconomic factors and automotive accidents. In sectional study, of 1613 reports analyzed, 232 (14.4%) were related to children and adolescents victims of automobile accidents. Head injuries occurred more frequently in children aged 0-4 years (53.8%, PR = 5.065) and pedestrians (30.4%, PR = 2.039), while face and maxillofacial injuries occurred in higher proportion among females (31.1%, PR = 0.489). Conclusions. There is evidence of a positive association between low socioeconomic status individual (income, education, unemployment) or the context (social deprivation, child mortality, income inequality, violence) and the morbidity and mortality resulting from automobile accidents involving children and adolescents. Accidents involving motorcyclists are more prevalent, affecting male adolescents 15-19 years, with higher frequency of lesions in the head and face.